The Influence of Financial Distress, Tax Planning and Good Corporate Governance (GCG) on Earnings Management with Internal Control as an Intervening Variable - Nofrianti Indah Pertiwi; Yuliansyah Yuliansyah; Muammar Khaddafi (Pusat Riset dan Inovasi Nasional, 2023)
Financial distress occurs due to the company's failure to manage finances. These continuous losses result in capital deficiencies and even worse conditions when the company's liabilities are much higher than the company's assets. The sample of this study was 126 BUMN companies selected using purposive samples. The results of the analysis and testing carried out can conclude that financial distress and good corporate governance affect internal control. At the same time, tax planning does not affect internal control. Then, financial distress, tax planning, and good corporate governance do not affect earnings management, while internal control affects earnings management. Furthermore, financial distress and good corporate governance affect earnings management through internal control, while tax planning does not affect earnings management through internal control.